2022
DOI: 10.1101/2022.11.21.515651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EEG-LLAMAS: an open source, low latency, EEG-fMRI neurofeedback platform

Abstract: Simultaneous EEG-fMRI is a powerful multimodal technique for imaging the brain, but its use in neurofeedback experiments has been limited by EEG noise caused by the MRI environment. Neurofeedback studies typically require analysis of EEG in real time, but EEG acquired inside the scanner is heavily contaminated with ballistocardiogram (BCG) artifact, a high-amplitude artifact locked to the cardiac cycle. Although techniques for removing BCG artifacts do exist, they are either not suited to real-time, low-latenc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…We also found that the computational complexity of this algorithm was sufficiently low for use in real-time experiments, as the time required to process a segment of data was lower than the duration of that segment. This result is unsurprising, as an analogous technique was previously used in real-time [ 51 ]. However, it is important to note that this processing time depends upon the specific hardware used to perform the computation, and performance will vary across individual implementations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We also found that the computational complexity of this algorithm was sufficiently low for use in real-time experiments, as the time required to process a segment of data was lower than the duration of that segment. This result is unsurprising, as an analogous technique was previously used in real-time [ 51 ]. However, it is important to note that this processing time depends upon the specific hardware used to perform the computation, and performance will vary across individual implementations.…”
Section: Discussionmentioning
confidence: 96%
“…However, in this work, we present a steerable spatial filter, rather than an FIR filter, that adaptively weighs all the motion sensor signals optimally or steers the weighted sum in the direction of minimal BCG noise. This type of spatial Kalman adaptive noise cancellation has been successfully applied to EEG/fMRI [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Artifact removal software is complex and mostly designed by private companies with closed-source code. Making such algorithms open-source or partially accessible to the public would enable improvements in the field (Levitt et al, 2022), potentially leading to advances such as an adapted individual-based artifact removal algorithm. Such a customized level would positively facilitate data pre-processing without compromising the EEG signal in special cases where artifact removal implies data loss.…”
Section: Sleep Neuroimaging Challenges and Future Directionsmentioning
confidence: 99%